The 2.7 resolution cryo-EM reconstruction of Mycobacterium tuberculosis encapsulin nanocompartment containing DyP peroxidase - Willmore, Rhys (Adolescent Health Research Institute, 2025)
Mycobacterium tuberculosis has evolved many persistence factors in response to the host generated immune response as a means of survival. One such immune response generated by humans is the use of reactive oxygen species (ROS) such as H2O2 to cause damage to M. tuberculosis. Encapsulin (from here on referred to as Enc) nanocompartments and the cargo proteins within have been implicated as persistence factors and decreased viability of cells has been shown when they are knocked out. Previous research has found that dye-decolorizing peroxidase (DyP) is encapsulated by these Enc nanocompartments, as has been shown in Mycobacterium smegmatis. This is done by way of a C-terminal targeting peptide, with Enc and DyP also being part of the same operon in the genome of M. tuberculosis. However, not much is understood about the structure and function of this system. Both encapsulin and DyP were expressed and purified recombinantly in E. coli. Cryo- EM particle processing and EM map reconstruction was carried in an attempt to generate a density map of encapsulated DyP along with model building. Native expression and purification were carried out followed by negative-stain EM on this sample.Successful recombinant expression and purification of DyP and Enc was achieved, with a high-resolution 2.7 Å cryo-EM structure of the Enc nanocompartment obtained, but no encapsulated DyP was visualized. A model of both the Enc monomer and multimer was built, with comparisons to M. smegmatis in charge around the fivefold pore showing differences. The purification of Enc from M. tuberculosis was successful and a negative stain reconstruction of the nanocompartment was obtained. 2D classes showed what could have been DyP but it did not show up in any 3D models. Ferritin was shown to only be outside of the nanocompartment. The high-resolution map showed high similarity to other T=1 Enc nanocompartments. The multimer model built called into question the exact function of this nanocompartment as the charge distribution differed from closely related M. smegmatis. When these charge changes are correlated to findings of catalytic analysis done in the same lab, it indicates that more research is needed to understand the exact function of this system in M. tuberculosis. The 2D classes showed that DyP is the only cargo protein that appears to be present in M. tuberculosis nanocompartments, with ferritin being identified outside the nanocompartment.